LOAFING: A CASE OF EMPLOYEE PERFORMANCE ISSUE: Received: 03rd May 2022; Revised: 02nd June 2022, 27th June 2022; Accepted: 29th June 2022 - Tugonon, Leo Roswald M (PEOPLE: International Journal of Social Sciences, 2022)
Employees are expected to be at work on time and perform their tasks to be productive. Otherwise, it is a performance issue, unauthorized absenteeism, or loafing. It is not only prevalent in private entities but also in government agencies. The Civil Service Commission (CSC) in the Philippine context is a government agency that discouraged loafing during work hours and limits the use of official time for non-related government tasks. The study utilized an observational research technique using a single case method where the participant was closely observed in the most natural settings in the workplace. The study investigates the performance of the employee and shows solutions to how the management addressed the issue. This case study presents an instance wherein an employee was reported by his co-employee (an informant) who committed loafing or frequent unauthorized absences from duty during office hours. Three alternative solutions are offered. First, refer the case to the Human Resource Management Officer who is a trained adjudicator, mediator, and conciliator. Second, determine the root cause of the problem and suggest an alternative course of action; and third, instead of imposing a harsh penalty of suspension or dismissal as the case may be, it would be appropriate for the management to subject the problem employee to an intervention program. There is a need to act with compassion and justice to ensure no repetitive action that may happen in the future.